1985
DOI: 10.1002/jsfa.2740360606
|View full text |Cite
|
Sign up to set email alerts
|

Protein quality and amino acid‐protein relationships of maize, sorghum and rice grain as influenced by nitrogen, phosphorus, potassium and soil moisture stress

Abstract: In pot and field experiments cereals were grown with greatly differing rates of N, P and K applications. For maize and sorghum, soil moisture levels were also varied. N applications, P-and K-deficiency, and moisture stress generally increased the total N content of grain, from 1.06 to 2.68, 1.01 to 2.42 and 0.81 to 2.33% (as % of DM) for maize, sorghum and rice, respectively. P, K and moisture stress affected the amino acid composition only indirectly through their effects on N concentration. In all three cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…A significant grain N increase with applied N dose was only observed in 2008, between treatments N0 and N1 (Table 2). Thiraporn et al (2008) also reported enhancement of maize grain N content with increasing dose of N (from 80 to 160 kg N/ha), while Eppendorfer et al (1985) detected an increase in total grain N from 1.06 to 2.68% N with the doses they applied. Positive correlations were found in our experiment between grain N content and the following essential amino acids: His (r = 0.688), Ile (r = 0.679), Leu (r = 0.698), Met (r = 0.628), Phe (r = 0.723), Val (r = 0.656) and the non-essential amino acids Ala (r = 0.660), and Glu (r = 0.744).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…A significant grain N increase with applied N dose was only observed in 2008, between treatments N0 and N1 (Table 2). Thiraporn et al (2008) also reported enhancement of maize grain N content with increasing dose of N (from 80 to 160 kg N/ha), while Eppendorfer et al (1985) detected an increase in total grain N from 1.06 to 2.68% N with the doses they applied. Positive correlations were found in our experiment between grain N content and the following essential amino acids: His (r = 0.688), Ile (r = 0.679), Leu (r = 0.698), Met (r = 0.628), Phe (r = 0.723), Val (r = 0.656) and the non-essential amino acids Ala (r = 0.660), and Glu (r = 0.744).…”
Section: Resultsmentioning
confidence: 91%
“…Seebauer et al (2004) reported that N supply (0 and 168 kg N/ha) had a variable effect on individual amino acid levels in young maize cobs. However increasing N concentrations were associated with decrease in crude protein of lysine, methionine, cystine, threonine, tryptophan and, generally, with increase in isoleucine, leucine, phenylalanine and glutamate (Eppendorfer et al 1985). Shewry (2007) reported that the nutritional quality of cereal grain also decreases with increasing grain protein content, as an increasing proportion of the nitrogen is incorporated into prolamin storage proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen fertilisation has been shown to increase CP content, but to have a negative effect on the content of most essential amino acids in the protein. The biological value of maize protein (Cromwell et al, 1983), wheat protein (Eppendorfer et al, 1985;Szúts et al, 1988) and sorghum protein (Eppendorfer et al, 1985) decreased as CP increased with high nitrogen fertiliser applications. This is due to an increase in the concentration of prolamine protein that has a low concentration of lysine, tryptophan and other essential amino acids (Ward & Allendale, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other factors such as the sugarcane cultivar, degree of maturity, soil type, and other cultivation factors, are also among the many sources of variation in the nutrient content of plant foods (Osagie and Onigbinde, 1998). Changes in the nutritional composition of plant foods caused by age, varietal and climatic/-environmental factors have long been recognized and documented (Bhatnager et al, 2004;Eppendorfer et al, 2006;Marques da Silva and Silva, 2006). Therefore some of the minor data variations observed may be location bound, since this study submits for the first time nutrients and chemical composition of sugarcane consumed in Calabar, Nigeria.…”
Section: Discussionmentioning
confidence: 91%